Formulation of Nanospanlastics as a Promising Approach for ‎Improving the Topical Delivery of a Natural Leukotriene Inhibitor (3-‎Acetyl-11-Keto-β-Boswellic Acid): Statistical Optimization, in vitro ‎Characterization, and ex vivo Permeation Study - Badria F; Mazyed E (Dove Medical Press, 2020)
Farid Badria,1 Eman Mazyed2 1Department of Pharmacognosy, Faculty of Pharmacy, Mansoura University, Mansoura, Egypt; 2Department of Pharmaceutical Technology, Faculty of Pharmacy, Kafrelsheikh University, Kafrelsheikh, EgyptCorrespondence: Eman MazyedDepartment of Pharmaceutical Technology, Faculty of Pharmacy, Kafrelsheikh University, POB 33516, Kafrelsheikh, EgyptTel +20 100 3484508Email eman_mazyad@pharm.kfs.edu.egPurpose: The current study aimed to discuss the potential of nanospanlastics as a surfactant-based vesicular system for improving the topical delivery of 3-acetyl-11-keto-β-boswellic acid (AKBA). AKBA is a potent anti-inflammatory drug, but it has poor oral bioavailability due to its poor aqueous solubility. Moreover, the topical delivery of AKBA is difficult due to its high lipophilicity. To overcome these drawbacks, AKBA was formulated as deformable elastic nanovesicles and nanospanlastics, for improving its topical delivery.Materials and Methods: AKBA-loaded spanlastic nanovesicles (SNVs) were formulated by ethanol injection technique according to 23 factorial design using Span 60 as a non-ionic surfactant and Tween 80 as edge activator (EA) to investigate the effect of different independent variables on entrapment efficiency (EE%), % drug released after 8 hr (Q8h) and particle size (PS) using Design-Expert software. In vitro characterization, stability test and ex vivo permeation study of the optimized formula were performed.Results: The choice of the optimized formula was based on the desirability criteria.‎ F7 was selected as the optimized formula because it has the highest desirability value of 0.648. F7 exhibited EE% of 90.04± 0.58%, Q8h of 96.87± 2.67%, PS of 255.8± 2.67 nm, and zeta potential of − 49.56 mV. F7 appeared as spherical well-defined vesicles in both scanning electron microscope (SEM) and transmission electron microscope (TEM). The Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) studies investigated the absence of interaction between AKBA and ‎different excipients and good encapsulation of AKBA within SNVs. F7 retained both physical and chemical stability after storage for 3 months at 4– 8 °C. Ex vivo permeation test exhibited significant enhancement of permeability of F7 across rat skin than the free drug.Conclusion: Nanospanlastics could be a promising approach for improving the permeability and topical delivery of AKBA.Keywords: AKBA, spanlastics, topical delivery, optimization, edge activator